Construção e ensaio de pórticos com tirante em madeira laminada colada - Possa, Desirè Coraça (2021)
The construction industry consumes a large amount of natural resources, generating a lot of waste and being responsible for a large part of the world’s environmental impacts. The use of wood in structures emerges as an environmentally friendly material in the construction and agricultural sector because it is a renewable constructive/structural material and its permanent use contributes to the reduction of carbon emissions in the atmosphere. The present study aimed to execute and test frames with ties, made of glued laminated timber and in a reduced scale, in order to evaluate their structural performance. The materials that were used are Pinus sp. wood and vegetable oil-based bicomponet adhesive in a 1:1.5 ratio of isocyanate and polyol, respectively. The characterization of the wood was carried out to obtain its physical and mechanical properties. For the execution of the units we adopted geometry similar to that used in previous research developed in LATEM. A French ceramic tile roof was used as a solution, employing the tie-rod due to the significant mass that this material imposes on the structure. Four frames were built with 3/8” threaded bar ties, with a free span of 1.9 meters and column height of 1.83 meters. The structures exhibited satisfactory performance regarding strength and stiffness. As for strength, the structures ruptured for an average load of 63.6 kN, approximately 1.37 times greater than the established verification load. As for stiffness, the structures exhibited smaller displacements when compared to the structures without the tie, reaching the normative limits for total loads of the order of 30 kN. In relation to the theoretical displacements, the frames presented significantly higher values. Furthermore, a positive correlation was obtained between the bulk density of the timber of the frames and their strength, exhibiting a correlation coefficient of around 0.95. Thus, the evidence obtained indicates that the use of the tension tie in the structures promoted an improvement in the mechanical performance in terms of strength and stiffness.